Socially Responsible Investment, Internal Financing Sources And Access To Bank Financing: Evidence From Indian Survey Data - Gill, Amarjit; S. Mand, Harvinder; Amiraslany, Afshin; Mathur, Neil (Asian Academy of Management (AAM), 2017)
We investigated the association between socially responsible investment, internal fnancing sources, and access to bank fnancing in the production industry of India. Using a survey research design, owners of small production frms were asked about their perceptions regarding socially responsible investment, internal fnancing sources, and access to bank fnancing. We found that socially responsible investment and internal fnancing sources help owners of small production frms improve access to bank fnancing. This study contributes to the literature on the relationship between socially responsible investment, internal fnancing sources, and access to bank fnancing. The fndings may be useful for fnancial managers, production frm owners, investors, consultants, and other stakeholders